Bahan Ajar PPKN Berbasis Karakter dan Literasi untuk Siswa Kelas IX SMP Al Hikmah Surabaya - Sriyanto; Ibut Priono Leksono; Harwanto Leksono (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
This study aims to produce teaching materials based on Character and Literacy PPKn Class IX students who are designed to be more interesting, to train independently, creatively and innovatively, according to students 'needs and develop students' competence, character and literacy. The development model used by Dick, Carey & Carey (2001) adjusted to the development needs. This analysis technique is used to process data obtained through evaluation sheets in the form of descriptive percentages. The validation results from learning design experts reached 92.5%. While the experts of teaching materials developed reached 89.3%. The results of trials on students, the overall eligibility percentage reached 83.66%. While the Review from the teacher reached 78.41% and the response through the questionnaire got a very good response. From the data and analysis that has been done, it can be concluded that the development product can be used as teaching material in Pancasila and Citizenship Education (PPKn) subjects that have very good qualifications, and develop the domains of competence, character and student literacy.